Autonomous Car Racing in Simulation Environment Using Deep Reinforcement Learning - Guckiran, Kivanc; Bolat, Bulent (IEEE, 2019)
Self-Driving Cars are, currently a hot topic throughout the globe thanks to the advancements in Deep Learning techniques on computer vision problems. Since driving simulations are fairly important before real life autonomous implementations, there are multiple driving-racing simulations for testing purposes. The Open Racing Car Simulation (TORCS) is a highly portable open source car racing-self-driving-simulation. While it can be used as a game in which human players compete with scripted agents, TORCS provides observation and action API to develop an artificial intelligence agent. This study explores near-optimal Deep Reinforcement Learning agents for TORCS environment using Soft Actor-Critic and Rainbow DQN algorithms, exploration and generalization techniques.
Keywords: Deep Reinforcement Learning; TORCS; Self-Driving Car; Computer Science